The Effect of Giving Early Stimulation on Child Development Aged 12-24 Months : Systematic Review - Intan Nur Laylatul Mufarrahah; Nunik Puspitasari; Irwanto (LPPM Universitas Harapan Bangsa, 2024)
Child development is a gradual change in body function with an increasing ability to make gross and fine movements, speak, and interact with the surrounding environment. In their development, children under two years of age still often experience growth and development disorders such as motor development disorders, language and communication development disorders, intellectual development disorders, and behavioral and emotional well-being disorders. This systematic review aims to giving information about the impact of offering stimulation on the growth of children aged 12-24 months, the systematic review adhered to the PRISMA guidelines the systematic review adhered to the Preferred Reporting tems for Systematic Review and Meta-Analysis (PRISMA) guidelines by filtering the titles and abstracts of the included articles using standard Microsoft Excel formulas. Multiple databases, including PubMed and ScienceDirect, were searched using appropriate keywords. Inclusion criteria encompassed English-written studies addressing pertinent subjects, presenting complete texts, and published within a specified timeframe.2018 to 2023. Five articles were reviewed with respondents aged 0-24 months. This article contains several types various kinds of stimulation, such as social interaction with children through talking and physical contact, then providing educational toys such as disassembling toys, puzzles, and story books, then introducing music and encouraging singing, drawing, and exploring the environment, such as providing appropriate challenges. with the child's level of development which can stimulate children's critical thinking abilities and creativity. It can be concluded from this study of several article that the government has attempted to improve child development to provide good care through daily stimulation to children, which also involves health service workers in improving children's growth and development